Indigenous knowledge of bush tea (Athrixia Phylicoides) and effect of fertigation frequency and growing medium on plant growth - Du Toit, Elsie Sophia (University of Pretoria, 2013)
Dissertation (MInstAgrar)--University of Pretoria, 2007.